2021
DOI: 10.3390/atmos12091179
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Volatilization, Forage Accumulation, and Nutritive Value of Marandu Palisade Grass Pastures in Different N Sources and Doses

Abstract: The reduction in ammonia (NH3) losses from volatilization has significant implications in forage production. The objective of this study was to evaluate the impact of N fertilizers (urea, ammonium nitrate, and ammonium sulfate) and four doses (0, 90, 180 and 270 kg N ha−1) on N losses by NH3 volatilization, accumulation, and forage chemical composition of Urochloa brizantha cv Marandu. Two field experiments were conducted to measure NH3 losses using semi-open chambers. The forage accumulation and chemical comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
1
7
0
3
Order By: Relevance
“…The proportion of volatilized N from AS fertilizer ranged between 18 and 21.5%, while the ammonia from the AN solution was hardly lost. This corresponds with the results of many studies [ 53 , 54 , 55 ]. The highest proportion of volatilized nitrogen in study of Liu et al [ 53 ] was recorded for ammonium sulphate applied under the drought conditions (20% of field capacity) at 20 °C.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The proportion of volatilized N from AS fertilizer ranged between 18 and 21.5%, while the ammonia from the AN solution was hardly lost. This corresponds with the results of many studies [ 53 , 54 , 55 ]. The highest proportion of volatilized nitrogen in study of Liu et al [ 53 ] was recorded for ammonium sulphate applied under the drought conditions (20% of field capacity) at 20 °C.…”
Section: Resultssupporting
confidence: 92%
“…He et al [ 56 ] described minimal ammonia volatilization at the initial soil pH of 3.5, which increased rapidly with increasing the pH up to 8.5. Correa et al [ 55 ] also presented a lower emission of NH 3 from AS fertilizer compared to the AN under the field experiment conditions. This result can be explained by the physiologically acidic reaction of the fertilizer, which makes the NH 4 + ions stable.…”
Section: Resultsmentioning
confidence: 83%
“…Ammonium sulfate and ammonium nitrate + calcium sulfate had the lowest accumulated losses of NH 3 -N in relation to the other N sources in both production environments ( Figure 4 ), due to the absence of N in the amidic form (NH 2 -N). Corrêa et al, Minato et al, and Otto et al [ 13 , 14 , 24 ] also obtained low losses due to NH 3 -N volatilization with the use of N sources in the ammoniacal and nitric forms, with losses ranging from 0.7 to 5.2% and 1.0 to 7.7% of the N applied for ammonium sulfate and ammonium nitrate, respectively, depending on the dose of applied topdressing. Following the increasing order of NH 3 -N emissions, Ur-formaldehyde was the enhanced-efficiency source that most reduced NH 3 -N volatilization, but it was less efficient than ammoniacal and nitric sources.…”
Section: Discussionmentioning
confidence: 95%
“…However, once applied to soil, urea is hydrolyzed by the action of urease enzyme, producing ammonia (NH 3 -N), which is rapidly lost to the atmosphere in the form of gas [ 6 ]. This loss may account for more than 60% of the N applied [ 7 ], depending on the soil and air temperature [ 8 ], soil moisture [ 9 ], soil pH [ 10 ], soil buffering capacity [ 11 ], presence of straw on the soil surface [ 12 ], N source [ 13 ], and rate of applied fertilizer N [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these large variations in the rate of NH 3 volatilization from urea are explained by several factors, like changes in weather conditions, such as air temperature and rainfall amount (BURCHILL et al, 2017;ENGEL et al, 2011;SANZ-COBENA et al, 2011;SIMAN et al, 2020), strong wind and moisture (NUNES et al, 2023), soil pH, application rate and placement depth (ROCHETTE et al, 2013). CORRÊA et al (2021) using urea fertilization at a rate of 270 kg N ha -1 in Marandu grass, reported 44.5% of N applied lost as NH 3 in a single dose; however, when it was divided into three applications, there was a reduction to 24.1% of N applied lost as NH 3 . For this reason, the NH 3 volatilization assessment from different weather conditions plays an important role in providing country-specific emissions data for agriculture inventory calculation.…”
Section: Introductionmentioning
confidence: 99%